Gummosis and Canker in Cashew (anacardium occidentale Linn.) - Singh, Sujan; Misra, B. M. (Indian Forester, 1980)
The cause of serious gummosis and canker disease of cashew (Anacardium occidentale) in Chingleput Forest Division, Tamil Nadu State, is identified as Hendersonna latoruloiea Nattrass. The pathogen is described in culture and also as it occurs in nature The disease symptoms include cankers on the bark, dark gray to black discolouration in Wood and abundant tyloses in the vessels, the cankers were successfully reproduced by artificial inoculations on plants of Morus alba Linn which is known to suffer from cankers due to H. toruloidea Measures to control the disease are outlined.